BRONCHIAL ASTHMA IN CHILDREN: CLINICAL COURSE AND TREATMENT APPROACHES - Mahmudov Qudratjon Xamidjon oʻgʻli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation Bronchial asthma in children is a chronic inflammatory disease of the airways characterized by recurrent episodes of wheezing, coughing, shortness of breath, and chest  tightness.  The  clinical  course  of  pediatric  asthma  varies  depending  on  age, severity of the disease, and exposure to triggering factors such as allergens, respiratory infections,  physical  activity,  and  environmental  pollutants.  Early  diagnosis  and continuous  monitoring  are  essential  for  effective  disease  control  and  prevention  of complications. Treatment approaches focus on long-term control and relief of acute symptoms through the use of inhaled corticosteroids, bronchodilators, and leukotriene modifiers,  combined  with  avoidance  of  triggers  and  patient  education.  A comprehensive,  individualized  management  strategy  improves  symptom  control, reduces exacerbations, and enhances the quality of life in children with asthma.